Hotspots of single-strand DNA “breakome” are enriched at transcriptional start sites of genes - Cao, Huifen; Zhang, Yufei; Cai, Ye; Tang, Lu; Gao, Fan; Xu, Dongyang; Kapranov, Philipp (Frontiers in Molecular Biosciences, 2022)
Single strand breaks (SSBs) represent one of the most common types of DNA damage yet not much is known about the genome landscapes of this type of DNA lesions in mammalian cells. Here, we found that SSBs are more likely to occur in certain positions of the human genome — SSB hotspots — in different cells of the same cell type and in different cell types. We hypothesize that the hotspots are likely to represent biologically relevant breaks. And, we found that the hotspots had a prominent tendency to be enriched in the immediate vicinity of transcriptional start sites (TSSs). We show that these hotspots are not likely to represent technical artifacts, or be caused by common mechanisms previously found to cause DNA cleavage at promoters, such as apoptotic DNA fragmentation or topoisomerase type II (TOP2) activity. Therefore, such TSS-associated hotspots could potentially be generated using a novel mechanism, that could involve preferential cleavage at cytosines, and their existence is consistent with recent studies suggesting a complex relationship between DNA damage and regulation of gene expression.